2019
DOI: 10.3390/c5030049
|View full text |Cite
|
Sign up to set email alerts
|

Growing Cities and Mass Participant Sport Events: Traveling Behaviors and Carbon Dioxide Emissions

Abstract: Fast-growing cities are expected to become a key contributor to the global climate crisis. A key characteristic of those urban districts is the accommodation of mass participant sport events. Sport entities, in collaboration with city governments, plan annually active participation sport events to promote their cities as tourism destinations. Mass participant sport events aim to attract more visitors to the cities and to establish a successful social and economically sustainable future to those places. Given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For example, the average carbon footprint of teams and fans participating in intercollegiate basketball competitions in 2019 was calculated as 201 million kg [58]. In another study focusing on the traveling of basketball fans in the USA, the carbon footprint of fan traveling during the entire season was calculated as 338 million kg [59]. In a study focusing on the travel-related carbon footprint of teams in the national basketball leagues of Turkey and Lithuania, the average carbon footprint of teams in both countries in a season was calculated as 53.02 tons [28].…”
Section: Discussion Of the Carbon Footprint Measures For Teams And Fansmentioning
confidence: 99%
“…For example, the average carbon footprint of teams and fans participating in intercollegiate basketball competitions in 2019 was calculated as 201 million kg [58]. In another study focusing on the traveling of basketball fans in the USA, the carbon footprint of fan traveling during the entire season was calculated as 338 million kg [59]. In a study focusing on the travel-related carbon footprint of teams in the national basketball leagues of Turkey and Lithuania, the average carbon footprint of teams in both countries in a season was calculated as 53.02 tons [28].…”
Section: Discussion Of the Carbon Footprint Measures For Teams And Fansmentioning
confidence: 99%
“…In a study focusing on the carbon footprint of fans attending sporting events for a year in South Carolina in the United States, it was found that the participants travelled more than 150 miles and the most important carbon footprint source was long-distance travel. In addition, the average carbon footprint of these long distance journeys was calculated as 338 million kg (Triantafyllidis and Davakos, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Incentives that promote greater car occupancy rates for medium‐distance (<800 km) “away” journeys and cycling to local events would reduce the overall CF of supporters 121 . This applies to those participating in mass participation (running) events 122 . Influencing the travel mode choice of local spectators and competitors has less benefit because of their relatively small contributions to the overall CF of events.…”
Section: Methodsmentioning
confidence: 99%
“… 121 This applies to those participating in mass participation (running) events. 122 Influencing the travel mode choice of local spectators and competitors has less benefit because of their relatively small contributions to the overall CF of events. During the 2022 Major League Baseball season, the 30 teams will clock up more than a million miles of travel.…”
Section: Methodsmentioning
confidence: 99%